2016
DOI: 10.1007/s10461-016-1546-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Social Self-Value Empowerment Intervention to Improve Quality of Life of HIV Infected People Receiving Antiretroviral Treatment in Nepal: A Randomized Controlled Trial

Abstract: We developed a comprehensive and culturally applicable empowerment intervention social self-value package with an aim to assess its efficacy in order to improve the quality of life (QoL) of HIV infected people receiving antiretroviral treatment. Participants were randomly allocated to receive either six weekly intervention sessions or standard care. Nonlinear mixed-effects models were performed to compare changes in empowerment scores over time. Between September and November 2014, 1447 individuals were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…Despite these limitations, there is evidence that a better QoL may in uence patient adherence to care and thus viral suppression achievement [66,67], which are necessary conditions for survival among PLWHA. Our results show that syndemic conditions mostly relate to psychological, social, and environment domains of QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, there is evidence that a better QoL may in uence patient adherence to care and thus viral suppression achievement [66,67], which are necessary conditions for survival among PLWHA. Our results show that syndemic conditions mostly relate to psychological, social, and environment domains of QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, there is evidence that a better QoL may in uence patient adherence to care and thus viral suppression achievement [66,67]…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Qiao et al concluded that policymakers needed to consider social support for female sex workers to protect them from HIV risks (Social support and condom use among female sex workers in China) (10). However, a study by Bhatta and Liabsuetrakul showed that social support could be a useful asset among HIV-infected patients to promote their quality of life, decrease stigma, and increase adherence to antiretroviral treatment (4).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing life expectancy in HIV-infected patients has been reported but high-risk behaviors have promoted the transmission risk of HIV among general populations (4). Studies have shown that HIV infection may remain asymptomatic in HIV-positive patients for a long time and the patients themselves may not be aware of their infection, which is another potential risk for other members of the society (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…This sample was calculated using the software Power and Precision (ver. 4) at a power of 80 and 95% confidence intervals considering the predictor variables PTSD (“Yes” response rate 28%) [ 37 ] and stigma (“Yes” response rate 75%) [ 38 ] as a reference with a 5% missing rate and 5% margin of error. Since the primary purpose of the present study was to assess the impact of the earthquake on PLHIV, we included PLHIV aged 18 years and older who, at the time of earthquake, had no ART treatment failure (no decrease in the CD4 count to the pre-therapy baseline, no HIV viral load >5000 copies/ml, or no serious opportunistic infections), were expected to be on ART for at least 6 months, and were on a first-line regimen.…”
Section: Methodsmentioning
confidence: 99%